C(sp3)−C(sp3) bond formation via nickel-catalyzed deoxygenative homo-coupling of aldehydes/ketones mediated by hydrazine - Dawei Cao (Nature Portfolio, 2021)
The direct deoxygenative coupling of aldehydes or ketones to construct C(sp3)−C(sp3) bond remains a scientific challenge. Here the authors use a nickel−catalyzed reductive homo-coupling of moisture- and air-stable hydrazones generated in-situ from naturally abundant aldehydes and ketones to construct challenging C(sp3)−C(sp3) bonds.